INOVASI PEMERINTAH KOTA DI DALAM PEMANFAATAN SAMPAH ORGANIK DI KOTA BANJAR - Rudiana Rudiana; Otong Husni Taufiq; Abdul Mutholib (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research was conducted because it is known that the City Government of Banjar still lacks innovation in the management of organic waste. Therefore, the objective of this research is to understand the innovations of the city government in utilizing organic waste in Banjar City. The method used is descriptive with a qualitative approach. The results of the study conclude that the City Government of Banjar has issued policies that formally regulate the management of organic waste, such as the Mayor's Regulation Number 18 of 2022. In addition, budget allocations in the local government budget for organic waste management programs are also available. However, this allocation is still limited and not yet fully adequate to meet all sustainable management needs. The implementation of organic waste sorting at the household level has started to be applied, especially in areas that have received socialization and assistance. However, the use of technology such as composters and biodigesters is still not optimal due to a lack of socialization, minimal technical personnel, and limited budgets and human resources. The processed organic waste products such as compost and maggot feed have been produced and utilized, but they have not developed to their full potential. The main obstacle lies in the weak marketing of the products and the absence of a sustainable distribution system. The City Government of Banjar has successfully raised public awareness through campaigns such as 'Waste Sorting Movement from Home' as well as utilizing social media and environmental slogans like 'Green Banjar'. This effort is considered successful because environmental messages have reached the public, although there is still a need for visual reinforcement such as the use of mascots.